Redıscovery of the Salvıa Haussknechtıı Boıss. (Lamıaceae) ın Kahramanmaraş from Türkıye (Bangladesh Journal of Botany, 2025)
The type specimen of Salvia haussknechtii Boiss., an endemic species of Türkiye, was first collected in 1865 by C. Haussknecht and later described by E. Boissier in 1879. Salvia haussknechtii Boiss. was poorly described based on type specimen of Haussknecht collected in 1865. Since then it could not be collected from elsewhere until 2022, when it was found on Berit Mountain. S. haussknechtii is only known from quite small population from Berit Mountain. It’s relationships and distinguishing characters from the closest relative S. caespitosa and S. multicaulis are discussed. The SEM shapes of pollen grains and seeds of S. haussknechtii are reported here for the first time. In addition, ecology, habitat, conservation status are given. For insufficient morphological structures of the type specimen, a new Topotype of S. haussknechtii is proposed.Bangladesh J. Bot. 54(1): 17-23, 2025 (March)